An Overview of Medical Malpractice Law in the United States Including Legislative and the Health Care Industry’s Responses to Increased Claims Authors - Heller, Thomas Allan (Collected Papers of Thomas A. Heller, 2025)
Medical Malpractice claims are frequently asserted in the United States. At various time and places, an extraordinarily high number of claims and payouts led to what some have called medical malpractice crises. Consequently, in some geographical locations physicians either could not purchase malpractice insurance as carriers withdrew from the market, or, insurance became increasingly expensive and the overall costs associated with the delivery of health care continued to rise. Other undesirable consequences of these crises included a shortage of qualified physicians in certain parts of the country. Many of the states responded to these problems legislatively through a long series of tort reform measures. The health care industry itself has evolved in numerous ways. In particular, many health care providers have turned away from traditional private insurance models to self-insured models such as captives. Further, the industry has continued to consolidate, with fewer, but larger hospitals and clinics, and with an increasing number of physicians employed directly by hospitals and large clinics. The results of all of these changes have had mixed results.